(untitled) (Publicacions de la Universitat de València, 2019)
The aim of this volume is to make a statement on the importance of research on Audiovisual Translation, both in its different varieties of production (dubbing, subtitling, surtitling, voice-over and e-learning) and in its relationship with language acquisition. On the whole, it is a merging of applied theory and practice, with a willingness to encourage a dialogue between scholars specialized in this field that may expand to other fields. El objetivo de este volumen es dar a conocer la importancia de la investigación sobre la Traducción Audiovisual, tanto en sus diferentes variedades de producción (doblaje, subtitulado, sobretitulado, locución y e-learning) como en su relación con la adquisición del lenguaje. En general, se trata de una fusión de teoría y práctica aplicadas, con la voluntad de fomentar un diálogo entre académicos especializados en este campo que pueda extenderse a otros campos.